2020
DOI: 10.5194/hess-24-771-2020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of initial conditions on convection-permitting simulations of a flood event over complex mountainous terrain

Abstract: Abstract. Western Norway suffered major flooding after 4 d of intense rainfall during the last week of October 2014. While events like this are expected to become more frequent and severe under a warming climate, convection-permitting scale models are showing their skill with respect to capturing their dynamics. Nevertheless, several sources of uncertainty need to be taken into account, including the impact of initial conditions on the precipitation pattern and discharge, especially over complex, mountainous t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 64 publications
(100 reference statements)
0
12
0
Order By: Relevance
“…In the rare cases when CPRCM domains are large such as over North America, the application of spectral nudging reduced 2‐m temperature biases, improved precipitation patterns, but suppressed precipitation intensity over the western U.S. Mountains (Liu et al, 2017). When CPRCMs are used to reproduce a specific meteorological event, often referred to as a case study, the use of spectral nudging in the intermediate RCM simulation is welcome to maintain the large‐scale atmospheric states of the driving reanalysis (Li, Pontoppidan, et al, 2020; Wootten et al, 2016).…”
Section: Methodology and Principles Behind Cprcmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rare cases when CPRCM domains are large such as over North America, the application of spectral nudging reduced 2‐m temperature biases, improved precipitation patterns, but suppressed precipitation intensity over the western U.S. Mountains (Liu et al, 2017). When CPRCMs are used to reproduce a specific meteorological event, often referred to as a case study, the use of spectral nudging in the intermediate RCM simulation is welcome to maintain the large‐scale atmospheric states of the driving reanalysis (Li, Pontoppidan, et al, 2020; Wootten et al, 2016).…”
Section: Methodology and Principles Behind Cprcmsmentioning
confidence: 99%
“…Kay et al (2015) attributed the lack of improvements on the simulated discharge to a wet bias in heavy precipitation over the UK, also reported in the Himalaya by Li, Gochis, et al (2017). In a series of sensitivity analyses focusing on the simulation of a flood event forced by a CPRCM in the mountains of western Norway, Li, Pontoppidan, et al (2020) simulated the correct peak flow volume and timing of the flood, which were sensitive to soil moisture and snow cover more than snow depth. In a study focusing on the water budget of two western Canada basins, Kurkute et al (2020) found that their CPRCM outperformed three reanalyses in balancing the surface water budget.…”
Section: Cprcm Benefits For Impact Studiesmentioning
confidence: 99%
“…The hindcast simulation period is from 1 June 2018 to 30 November 2018, with the first 45 days for warm-up and the rest for comparison. The reason for setting such a long warm-up time is that 1.5 spin-up days are needed for precipitation, but a much more extended period is necessary for discharge due to the influence of soil moisture [70].…”
Section: Coupled Simulationsmentioning
confidence: 99%
“…More specifically, it parameterizes overland and river flow routing and subsurface routing in the 2 m soil column, while it also includes a groundwater bucket model, thus providing a feedback between terrestrial hydrology and land-atmosphere interactions in the WRF system. The WRF-Hydro model has been used in numerous flood-related research applications (Senatore et al, 2020;Papaioannou et al, 2019;Varlas et al, 2019;Avolio et al, 2019;Lin et al, 2018;Silver et al, 2017;Xiang et al, 2017;Arnault et al, 2016;Givati et al, 2016;Wagner et al, 2016;Senatore et al, 2015;Yucel et al, 2015) and for operational flood forecasting in the United States (Krajewski et al, 2017;NOAA, 2016) and Israel (Givati and Sapir, 2014). In particular, in the Mediterranean area, Senatore et al (2020) implemented WRF-Hydro in a catchment of Italy in order to highlight the impact of sea surface temperature (SST) in operational forecasts.…”
Section: Introductionmentioning
confidence: 99%